Detecting the historical roots of research fields by reference publication year spectroscopy (RPYS) - Marx, Werner; Bornmann, Lutz; Barth, Andreas; Leydesdorff, Loet (Journal of the Association for Information Science and Technology, 2014)
We introduce the quantitative method named “Reference Publication Year Spectroscopy” (RPYS). With this method one can determine the historical roots of research fields and quantify their impact on current research. RPYS is based on the analysis of the frequency with which references are cited in the publications of a specific research field in terms of the publication years of these cited references. The origins show up in the form of more or less pronounced peaks mostly caused by individual publications that are cited particularly frequently. In this study, we use research on graphene and on solar cells to illustrate how RPYS functions, and what results it can deliver.